MAYORAZGO Y VINCULACIÓN DE LA PROPIEDAD SEÑORIAL EN MURCIA A FINES DE LA EDAD MEDIA - García Díaz, Isabel (Miscelánea Medieval Murciana, 1989)
An analysis is made of entailed estates in the kingdom of Murcia in the Lower Middle Ages, that is, prior to the passing of legislation regulating such institutions in Castile at the Cortes de Toro in 1505. The four estates studied, all belonging to the Murcia oligarchy, are: Cotillas, the property of the Calvillo-Carrillos; La Ñora, which belonged to the Arróniz family; the Fajardo estate and that of the Montealegre family in the place of that name.The study shows the problems of founding in the kingdom of Murcia states wich the global binding condition of those in the Crown of Castile and hinglinghts the features which brought them more into Une with the Catalán-Valencian model